2012
DOI: 10.3899/jrheum.111143
|View full text |Cite
|
Sign up to set email alerts
|

CCL18 — Potential Biomarker of Fibroinflammatory Activity in Chronic Periaortitis

Abstract: Serum concentration of CCL18 reflects fibroinflammatory activity and extent of disease in patients with chronic periaortitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…Furthermore, enhanced CCL18 production has been demonstrated in several human diseases, including various malignancies and inflammatory joint, lung, skin, and vessel diseases (). A recent study also showed that serum CCL18 concentrations reflected fibroinflammatory activity and extent of disease in patients with chronic periaortitis ().…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, enhanced CCL18 production has been demonstrated in several human diseases, including various malignancies and inflammatory joint, lung, skin, and vessel diseases (). A recent study also showed that serum CCL18 concentrations reflected fibroinflammatory activity and extent of disease in patients with chronic periaortitis ().…”
Section: Discussionmentioning
confidence: 96%
“…We analyzed the release of key inflammatory cytokines at days 1, 3 and 6 of incubation by ELISA and the expression of key surface markers by immunofluorescence and confocal microscopy. As key inflammatory cytokines we took TNF-α (marker of M1 response) and CCL18 (marker of M2 response) which are shown to take part in chronic inflammation [102,103]. For the study of surface markers, we analyzed the expression of CD206 (marker of M2 response, strongly up-regulated in macrophages during chronic inflammation [104]) and stabilin-1 (marker of M2 response with tolerogenic functions [38]).…”
Section: Application Of Ex Vivo Monocyte-based Test Systemmentioning
confidence: 99%
“…CCL18 is mainly expressed and spontaneously secreted by cancer cells and stoma cells including monocytes, macrophages and immature dendritic cells etc. CCL18 secreted from M2-type TAMs is increased not only in chronic inflammations 24, fibrotic diseases 25, 26 and white adipose tissue dysfunction 27, but also in various types of neoplastic diseases. Song's team determined that serum CCL18 was obviously elevated in patients with breast carcinoma, and high CCL18 in the serum was linked with lymph node metastasis and worse histopathological typing, which was an independent influencing factor in the prognosis of patients with breast cancer 12.…”
Section: Discussionmentioning
confidence: 99%